(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article examines issues related to the participation of third parties in civil proceedings. It describes the legal status of third parties, how they can intervene in a case, and what rights and obligations they have. Special attention is given to the differences between third parties asserting independent claims in the dispute and those who do not. The article also discusses the procedural position of third parties and their role in civil proceedings. It emphasizes the importance of third-party participation in protecting their rights and interests in judicial proceedings.